The Influence of Financial Technology Management on Financial Performance: The Moderating Role of Digital Literacy - Reni Nurlaela (Yayasan Ilomata, 2026)
The development of financial technology (fintech) has accelerated digitalization in financial institutions and requires more strategic technology management to strengthen financial outcomes. However, large technology investments do not automatically translate into better performance if they are not matched by employees’ ability to understand and operate the technology. This study therefore examines whether financial technology management is associated with financial performance and whether digital literacy moderates this association. Using a quantitative design and partial least squares structural equation modeling (PLS‑SEM) with WarpPLS, survey data were collected from 200 bank employees directly involved in fintech use and management in Indonesian financial institutions. The measurement model was assessed through indicator loadings, composite reliability, and average variance extracted (AVE), while the structural model evaluation focused on path coefficients, the coefficient of determination (R²), predictive relevance (Q²), and the interaction term for moderation. The results indicate a positive and statistically significant association between financial technology management and financial performance based on PLS‑SEM estimates, and show that higher digital literacy strengthens this relationship. Employees with stronger digital literacy are better able to operate fintech applications accurately, reduce technical errors, and exploit data‑driven analytics in ways that are reflected in higher perceived financial performance, whereas low digital literacy constrains the effective use of financial technology and is associated with lower perceived outcomes. These findings suggest that successful fintech initiatives depend not only on the sophistication of systems but also on the digital capabilities of users. Strengthening digital literacy should therefore be treated as a core strategic lever to ensure that financial technology management contributes to sustained improvements in financial performance.